2018
DOI: 10.1002/mde.2980
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of moral hazard in research and development supply relations: Empirical results beyond the agency‐theory explanation

Abstract: Moral hazard can hinder both the realization and the effectiveness of research and development (R&D) supply relations. However, to the best of our knowledge, there have been no empirical studies investigating the determinants of moral hazard under the specific circumstances of R&D supply relations. Based on a study on 104 cases, this article will help to fill that gap. The results not only confirm information asymmetries as determinants, as predicted by principal‐agent theory, but also reveal surprising effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 114 publications
(231 reference statements)
0
6
0
2
Order By: Relevance
“…Throughout 2018, oil shortages persisted and supported price increases, which only slowed in the fourth quarter [29][30][31][32]. However, this did not prevent the average annual price from increasing by almost a third -up to 69.8 dollars per barrel.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout 2018, oil shortages persisted and supported price increases, which only slowed in the fourth quarter [29][30][31][32]. However, this did not prevent the average annual price from increasing by almost a third -up to 69.8 dollars per barrel.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, they developed Cenomanian deposits of relatively simple geological structure, containing easily recoverable "dry" gas. The degree of depletion of the main gas horizon is growing every year in 2018 the Cenomanian deposits provided no more than two-thirds of the NTRP gas production (Pillay, 2014;Kloyer et al, 2019;Flynn et al, 2016). The gas reserves of other oil and gas complexes of the NTRP are mostly difficult to recover.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers observed that information asymmetry, internal uncertainty, and one-sided dependence increase the potential for opportunism due to the establishment of power asymmetries between partners (Kloyer, Helm, & Aust, 2019). In such a context, they may withdraw from cooperation and act only according to their interests (Williamson, 1985).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The affective trust dimension may have contributed to the closure of the relationship due to its focus on emotions and feelings, as the latter may favor not demanding transparency, as was the case. In addition, they can accentuate information asymmetry between the parties and, consequently, increase the potential for opportunism (Kloyer et al, 2019).…”
Section: Strong Type Affective Nomentioning
confidence: 99%